Uptake of insurance services as a risk management tool among Small and Medium Enterprises (SMEs) in Dodoma-Tanzania - Macha , Julius J. (International Journal of Accounting, Finance and Business, 2025)
Small and medium enterprises (SMEs) around the globe conduct businesses mainly in a highly uncertain environment, facing a wide range of risks and uncertainties. Despite of the risk still few SMEs have adequate insurance policy cover for the risks exposed to. Thus, this study investigates factors that influence uptake of insurance services among Small and medium enterprises as a risk management tool at Dodoma region in Tanzania. Research framework based on diffusion of innovation (DOI) theory was adapted in this study. Convenient sampling technique was employed to draw primary data from 193 SMEs by using closed-ended survey questionnaire. Partial least squares structural equation modeling (PLS-SEM) was utilized for data analysis and hypotheses testing, with Smart PLS4.0 facilitating the process. The study results confirmed that awareness and insurance product design have positive and significant impact on uptake of insurance services among Small and medium enterprises. However, perceived cost was found to have negative and insignificant impact on Small and medium enterprises to use insurance services. The study recommends that policy makers should design policies and strategies that could enhance product design which are tailored to Small and medium enterprises. In addition, they should implement a variety of awareness campaigns across different media platforms, utilizing simple Tanzanian national language to ensure comprehension by the majority.